Social Adaptation Service for Veterans and their Families: the Experience of Providing and Perspectives of Development in Ukraine - Slozanska, Hanna; Biront, Olesya (Social work and education, 2025)
The article analyzes the current state and mechanisms of providing social adaptation services for war veterans and their family members within the framework of state veteran policy implementation. The legal and regulatory framework governing the procedure for providing this service, including state standards for social adaptation, is reviewed. The study examines the regulatory support and the state standard that regulate this sphere. An empirical study was conducted to explore the specific characteristics of providing social adaptation services to veterans and their families at the level of territorial communities in Ukraine. The prevalence and existing mechanisms for delivering these services were examined. The article investigates the institutional features of local support provision, identifies successful models of social protection, and highlights the primary challenges and needs of social work professionals in the context of providing these services. The key barriers hindering the effective adaptation of veterans within communities are identified. Based on the analysis of practical experience and identified problems, recommendations have been developed to improve the system of social adaptation for veterans during their transition from military to civilian life, as well as for their family members in Ukraine. Specific ways to optimize interagency cooperation, enhance staff qualifications, and ensure universal access to high-quality services are proposed, taking into account the contemporary challenges of the wartime and post-war periods.